User Knowledge, Data Modelling, and Visualization: Handling through the Fuzzy Logic-Based Approach. (26th February 2021) - Liao, Xiaoqun; Nazir, Shah; Zhou, Yangbin; Shafiq, Muhammad; Qi, Xuelin
Abstract : In modern day technology, the level of knowledge is increasing day by day. This increase is in terms of volume, velocity, and variety. Understanding of such knowledge is a dire need of an individual to extract meaningful insight from it. With the advancement in computer and image-based technologies, visualization becomes one of the most significant platforms to extract, interpret, and communicate information. In data modelling, visualization is the process of extracting knowledge to reveal the detail data structure and process of data. The proposed study aim is to know about the user knowledge, data modelling, and visualization by handling through the fuzzy logic-based approach. The experimental setup is validated through the data user modelling dataset available in the UCI web repository. The results show that the model is effective and efficient in situations where uncertainty and complexity arise.